THE EFFECTIVENESS OF VIEWING A BALLOON-BLOWING VIDEO IN INCREASING THE PEAK EXPIRATORY FLOW AMONG ASTHMA PATIENTS AT THE MAKASSAR LUNG HEALTH CENTER - Serlina Sandi; Jenita Laurensia Saranga; Erpin Randa; Sintike Sintike (Universitas Pelita Harapan, 2022)
Asthma is one of the deadliest diseases in Indonesia of which the prevalence continues to increase and influence the country’s economic burden. Appropriate intervention is needed to prevent recurrence. This study aims to analyse the effectiveness of Balloon Blowing (BB) video instruction on the Peak Expiratory Flow (PEF) of asthmatic patients at the Makassar Lung Health Centre. This research was done quantitatively using a quasi-experimental design approach, as well as using one pre- and post-test group, namely the Balloon Blowing Group. The sampling technique was Consecutive Sampling with a total of 22 samples that met the inclusion criteria. Before conducting the Balloon Blowing exercise, the researchers measured the Peak Expiratory Flow value using a Peak Flow Meter (PFM). Balloon Blowing intervention was then given five times a week for two weeks according to the video guidelines. Data analysis using the Wilcoxon test showed that there was a significant difference in the Peak Expiratory Flow value before and after the Balloon Blowing intervention (ρ =0.000, ρ <0.05). Thus, the Balloon Blowing exercise is effective in increasing the Peak Expiratory Flow value in asthmatic patients.